Coronary perfusion pressure and compression quality in maternal cardiopulmonary resuscitation in supine and left-lateral tilt positions: A prospective, crossover study using mannequins and swine models. (September 2017) - Dohi, Satoshi; Ichizuka, Kiyotake; Matsuoka, Ryu; Seo, Kohei; Nagatsuka, Masaaki; Sekizawa, Akihiko
Abstract: Objective: The risk of maternal and fetal mortality is high if cardiopulmonary arrest occurs during pregnancy. To assess the best position for maternal cardiopulmonary resuscitation (CPR), a prospective randomized crossover study was undertaken, involving basic life support mannequin-based simulation (BLS-MS) and a swine model of pulseless electrical activity (an unstable cardiac state) incorporating a fetal mannequin (PEA-FM). Study design: The BLS-MS (performed by certified rescuers) served to evaluate the quality of chest compressions in 30° left lateral tilt (LLT) and supine positions. Based on a 5-point scale, each rescuer subjectively graded their experience. The PEA-FM model was used to compare coronary perfusion pressure readings during CPR in supine, supine with left uterine displacement, 30° LLT, and 30° right lateral tilt positions. Compression rate and correctness of hand position, compression depth, and recoil were measures of compression quality (BLS-MS). Results: Compared with LLT position, supine position enabled correct hand position (rate: 0.99 vs 0.88; p <  0.05) and compression depth (rate: 0.76 vs 0.36; p <  0.001) significantly more often. Moreover, BLS-MS rescuers found chest compressions significantly easier to perform with the mannequin in supine (vs LLT) position (difficulty score: 1.75 vs 3.95; p <  0.001). In the PEA-FM study arm, supine position with left uterine displacement and right lateral tilt positions had the highest and lowest recorded coronary perfusion pressure readings, respectively. Conclusion: Supine position with left uterine displacement is optimal for maternal CPR.